(1)Direct comparison of a genetically encoded sensor and small molecule indicator: implications for quantification of cytosolic Zn(2+) - Qin, Yan (2013)
Fluorescent sensors are powerful tools for visualizing and quantifying molecules and ions in living cells. A variety of small molecule and genetically encoded sensors have been developed for studying intracellular Zn(2+) homeostasis and signaling, but no direct comparisons exist making it challenging for researchers to identify the appropriate sensor for a given application. Here we directly compare the widely used small molecule probe FluoZin-3 and a genetically encoded sensor, ZapCY2. We demonstrate that, in contrast to FluoZin-3, ZapCY2 exhibits a well defined cytosolic localization, provides estimates of Zn(2+) concentration with little variability, does not perturb cytosolic Zn(2+) levels, and exhibits rapid Zn(2+) response dynamics. ZapCY2 was used to measure Zn(2+) concentrations in 5 different cell types, revealing higher cytosolic Zn(2+) levels in prostate cancer cells compared to normal prostate cells (although the total zinc is reduced in prostate cancer cells) , suggesting distinct regulatory mechanisms.